(untitled) (Revista "Boletín el Conuco", 2022)
The dimensions of violence have been axes and topics of discussion in security policies. In the case of the media and internaut dimensions, their relevance lies in the prevention of violence in electronic networks. Studies on violence on Facebook highlight that bullying is less likely if contact requests are regulated. On Twitter, violence is contained with specific guidelines for harassment or intimidation. On YouTube, content complaints moderate violence. On TikTok, the dynamics of the content inhibit its influence on reactions. On Instagram, the contents are displayed according to the user’s profile. On WhatsApp, the stigmatization of messages and senders underestimates their potential. However, the relationship between Internet violence and other violence has not been explained. Therefore, the objective of the study will be the empirical test of a trajectory model to predict the prevention of violence in social digital networks. A psychometric, cross-sectional and correlational study was carried out with a selection of 100 students. The results show that violence on the Internet is associated to a lesser extent with other dimensions of violence and does not transfer its incidence in its prevention. In relation to the literature from 2019 to 2022, communication and risk control policies are recommended.